(untitled) (World Bulletin of Public Health, 2025)
According to the assessment of the nutritional status of patients with oral cavity cancer (OCC), the average number of meals per day was 3.5 ± 0.1. By type of nutrition: 40 patients (85.1%) had natural (oral) feeding, 5 (10.6%) mixed (combined), and 2 (4.2%) enteral feeding. In 40.0% of patients, meat and meat products; in 50.0%, grains and cereals; in 37.0%, vegetables and gourds; in 17.0%, fruits; in 52.0%, legumes; and in 37.0%, milk and dairy products were consumed below physiological norms. The following were consumed above physiological norms: 15.0% confectionery products, 55.0% bread and high-grade flour products, 60.0% fast food and processed products, 20.0% chemically processed products, 12.0% spicy and salty foods, and 17.0% carbonated and colored drinks. This may reduce immune system function and increase the risk of cancer development and complications